Critical thinking patterns in students after exposure to an integrated model of nursing education - Gordón de Isaacs, Lydia (Investigación y Educación en Enfermería, 2010)
<!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]--> Objective. To determine critical thinking patterns manifested by a group of nursing students of the University of Panama after being exposed for a semester to the teaching- learning process using a Teaching Model for Developing Critical Thinking Skills in Nursing (TMDCTSN). Methodology. Qualitative study in which through participant observation critical thinking patterns expressed by the group of students during the course of the last module of the semester were recorded in journals. The emerging patterns were classified in categories according to the critical thinking skills described by the TMDCTSN. Results. It was found that students showed critical thinking patterns according to the eight skills described in the critical thinking teaching model in nursing. Conclusion. The model can be used to develop critical thinking skills in nursing.